Self-Motivation Moderation of Accounting Information Systems and Performance of Small and Medium-Sized Micro Enterprises - Een yualika ekmarinda; Ria Meilan; Octavia Widya Alfanasari (Jurnal Ekonomi, 2024)
Self-motivation is part of emotional intelligence. Development consisting of self-motivation, empathy, social skills is expected to be able to improve the performance of small and medium-sized enterprises. The research aims to explore empirically how accounting information systems influence the performance of small and medium-sized enterprises by using self-motivation as a moderation tool. The sample method used in this study is convenience sampling. The Slovenian formula can be used to determine the number of samples required. The data analysis technique used is the analysis of the method Partal Least Squares (PLS). According to the analysis of this study, showing accounting information systems have a positive influence on the performance of small enterprises.